Molecular Simulation of Adsorption Characteristics of Pb2+ and Zn2+ in Modified Kaolinite - Shaohang CHEN; Xiaohong FANG; Fangui ZENG; Xiaojun LI (Kuangchan zonghe liyong, 2024)
This is an article in the field of mining engineering. In order to explore the adsorption mechanism of heavy metal ions Pb2+ and Zn2+ in kaolinite urea intercalation complex, molecular simulation was used to simulate Pb2+ and Zn2+ in single system and coexistence system at 268, 283, 298 K under constant pressure of 0.1 MPa. The results showed that when Pb2+ and Zn2+ were adsorbed separately, the adsorption capacity decreased with the increase of temperature, and the isosteric adsorption heat also had the same trend. The adsorption capacity and isosteric adsorption heat were Pb2+>Zn2+, and the self diffusion coefficient increased with the increase of temperature, and Zn2+>Pb2+; In the competitive adsorption, the change law was consistent with that of single adsorption, the adsorption capacity and isotherm of Pb2+ and Zn2+ were lower than those of the single adsorption, and the self diffusion coefficient was higher than that of the single adsorption, which indicated that there was competitive adsorption between them.